Evaluation of the Implementation of Regional Regulation Number 1 of 2019 on the Rehabilitation of Victims of Narcotics, Psychotropic Substances, and Other Addictive Substances Abuse - Taufik Ismail, Muhammad; Samran; Sri Melda Br Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The abuse of Narcotics, Psychotropic Substances, and Other Addictive Substances (NAPZA) in North Sumatra Province has become a serious issue. To address this, Regional Regulation Number 1 of 2019 was enacted, aiming to improve the rehabilitation of NAPZA victims. However, the implementation of this policy still faces challenges, such as ineffective intersectoral coordination, limited funding, and insufficient training for rehabilitation staff. These issues hinder the effectiveness of rehabilitation programs and the social reintegration of former NAPZA users. Research Objectives: This study aims to analyze the implementation of Regional Regulation Number 1 of 2019, identify the barriers in rehabilitating NAPZA victims in North Sumatra, and provide policy alternatives to address these barriers and improve the effectiveness of rehabilitation programs. Research Methodology: This research uses Grounded Theory with a qualitative approach. Data were collected through interviews with government officials, rehabilitation staff, and relevant committees. To determine priority policies, the researcher also employed the Analytical Hierarchy Process (AHP). Research Findings: The findings show that weak intersectoral coordination, limited funding, and insufficient training for rehabilitation staff are the main barriers. Additionally, social stigma towards former NAPZA users exacerbates their social reintegration. Conclusion: Enhancing intersectoral coordination, increasing funding, and providing continuous training for rehabilitation staff are necessary to improve the implementation of the regulation. The post-rehabilitation program, based on economic empowerment, must be strengthened to support better social reintegration.